Production of multiple biofuels from whole camelina material: a renewable energy crop - Mohammad, Balsam T.; Al-Shannag, Mohammad; Alnaief, Mohammad; Singh, Lakhveer; Singsaas, Eric; Alkasrawi, Malek (North Carolina State University, 2018)
Camelina sativa is a cool-season oil seed crop that has been proven to produce various biofuels. The present study investigated the technical possibilities of using whole camelina biomass as a model feedstock in a biorefinery. This investigation examined the possibilities of using camelina seeds as a source of oil for biodiesel, sugars for ethanol, and meal for one-portfolio products. The camelina harvest residues (straw) can serve as the main source for green sugars. This study found that the energy input for the whole biorefinery process was 25.1 MJ/L ethanol, while the energy output was 54.3 MJ/L ethanol. The net energy ratio of 2.16 MJ/L ethanol was found to be competitive with other energy crops. The process was environmentally friendly, and it reduced greenhouse gas emissions by 40% if the produced biodiesel replaced petroleum diesel. The seed meals and glycerin were found to be a good source of revenue as high value-added products and can provide an additional revenue of $1/kg of produced oil.